PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN MAGIC STRAW TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS V SD - Riska Zulfa Luthfiyyah; Hafiziani Eka Putri; Nadia Tiara Antik Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted because of the existence of mathematical problems, especially in students' creative thinking skills. This study aims to determine the effect of Realistic Mathematics Education approach assisted by magic straw learning media on students' mathematical creative thinking skills in grade V elementary school. This research used quasi experiment method with nonequivalent control group design. The population of this study were fifth grade students in Karawang Regency with a total sample size of 54 students. Based on the results of the study, it shows that the RME approach assisted by magic straw has a significant effect on mathematical creative thinking skills by comparing pre-test and post-test scores. The results obtained an effect of 47.8% while 52.2% was influenced by other factors. So that the RME approach can be used as an alternative solution to learning approaches in improving the mathematical creative thinking skills students.